Enhancing engineering students' ethical reasoning: Situating reflexive principlism within the SIRA framework. Issue 1 (26th February 2019) - Hess, Justin L.; Beever, Jonathan; Zoltowski, Carla B.; Kisselburgh, Lorraine; Brightman, Andrew O.
Abstract: Background: Educating engineers to reason through the ethical decisions they encounter when developing or implementing new technologies is a critical challenge. However, engineering educators have not widely adopted a framework for preparing engineering students to analyze ethical issues. Purpose/Hypothesis: We developed and tested an approach for enhancing the ethical reasoning of engineering students. This approach integrates reflexive principlism, an ethical reasoning approach, within a structured learning framework, scaffolded, interactive, and reflective analysis, or SIRA. We hypothesized that students' ethical reasoning abilities and empathic perspective‐taking tendencies would increase. Design/Method: We implemented and tested the integrated approach over five semesters with graduate‐level engineering students through a quasi‐experimental, controlled research design. We measured changes in ethical reasoning using the Engineering Ethical Reasoning Instrument (EERI) and the Defining Issues Test 2 (DIT2) and empathic tendencies using the Interpersonal Reactivity Index (IRI). We examined relationships among measures through correlation analysis. Results: The EERI instrumentation indicated that the approach significantly increased the ethical reasoning abilities of graduate‐level engineering students. However, the DIT2 findings did not indicate change. The IRI indicated perspective‐taking tendencies were enhanced and personal distress tendencies were reduced. Postcourse correlational data indicated moderate relationships between perspective‐taking and ethical reasoning as measured by the IRI and the EERI indexes. Conclusions: This study provides a theoretical approach for developing ethical reasoning and empathic perspective‐taking among graduate‐level engineering students. It also provides a theoretical framework, a pedagogical approach, and evaluation methods that others may utilize.